Characteristics of Problem-Based Learning in the Development of Critical Thinking Skills: A Systematic Review. - Macías Mendoza, Jacqueline; Batista Garcet, Yoiler; Villavicencio Cedeño, Lisette Beatriz (Spanish Journal of Medical Education, 2025)
Background: Developing critical thinking is a major challenge in medical education, where evidence-based decision-making is fundamental for clinical practice. Problem-Based Learning (PBL) has evolved into a pedagogical strategy that integrates inquiry, reasoning, and reflection. Although classical meta-analyses have shown its benefits in knowledge transfer and integration, there remains a need to assess its specific impact on critical thinking within health sciences education. Objective: To analyze the characteristics of PBL and its influence on the development of critical thinking skills in medical and health sciences students. Methods: Systematic review conducted in accordance with PRISMA 2020 guidelines. Searches were performed in PubMed, Scopus, and CINAHL between January 2000 and December 2024, in English and Spanish. A total of 78 records were retrieved; after removing duplicates and applying inclusion/exclusion criteria, 18 studies were included in the qualitative synthesis. Results: Interventions (8–16 weeks) applied classical PBL and derived models such as 3C3R and IDEAS. Significant improvements were reported in cognitive skills (interpretation, analysis, evaluation, inference, explanation, and self-regulation) and attitudinal dispositions (critical reflection, inquiry, curiosity, and autonomous learning). In medical education, the most evident outcomes were enhanced clinical reasoning and evidence-based decision-making. Conclusions: PBL is an effective methodology to foster critical thinking among medical students, consolidating itself as a structural component of medical education. Systematic curricular integration and multicenter, longitudinal studies are recommended to strengthen evidence across diverse clinical and educational contexts.